Impact of the COVID-19 pandemic on paediatric patients with cancer in low-income, middle-income and high-income countries: protocol for a multicentre, international, observational cohort study. Issue 6 (2nd June 2021) - Peter, Noel; Bandyopadhyay, Soham; Lakhoo, Kokila
Abstract : Introduction: Childhood cancers are a leading cause of non-communicable disease deaths for children around the world. The COVID-19 pandemic may have impacted on global children's cancer services, which can have consequences for childhood cancer outcomes. The Global Health Research Group on Children's Non-Communicable Diseases is currently undertaking the first international cohort study to determine the variation in paediatric cancer management during the COVID-19 pandemic, and the short-term to medium-term impacts on childhood cancer outcomes. Methods and analysis: This is a multicentre, international cohort study that will use routinely collected hospital data in a deidentified and anonymised form. Patients will be recruited consecutively into the study, with a 12-month follow-up period. Patients will be included if they are below the age of 18 years and undergoing anticancer treatment for the following cancers: acute lymphoblastic leukaemia, Burkitt lymphoma, Hodgkin lymphoma, Wilms tumour, sarcoma, retinoblastoma, gliomas, medulloblastomas and neuroblastomas. Patients must be newly presented or must be undergoing active anticancer treatment from 12 March 2020 to 12 December 2020. The primary objective of the study was to determine all-cause mortality rates of 30 days, 90 days and 12 months. This study will examine the factors that influenced these outcomes. χ 2 analysis will be used to compare mortality between low-income and middle-income countries and high-income countries. Multilevel, multivariable logistic regression analysis will be undertaken to identify patient-level and hospital-level factors affecting outcomes with adjustment for confounding factors. Ethics and dissemination: At the host centre, this study was deemed to be exempt from ethical committee approval due to the use of anonymised registry data. At other centres, participating collaborators have gained local approvals in accordance with their institutional ethical regulations. Collaborators will be encouraged to present the results locally, nationally and internationally. The results will be submitted for publication in a peer-reviewed journal.